Descriptive analysis of the ‘relictual’ Mediterranean landscape in the Guadalquivir River valley (southern Spain): a baseline for scientific research and the development of conservation action plans - Aparicio, Abelardo (Biodiversity and Conservation, 2007)
Landscape fragmentation is ancient and severe in the countryside of the Guadalquivir river valley (Western Andalusia, Southern Spain). BIANDOCC is a project that aims to inventory all the forest patches embedded in this anthropogenic area to record quantitative, qualitative, and descriptive information about management, conservation status, vegetation physiognomy and Xoristic richness. We have characterized a ‘relictual’ landscape (t1% of habitat retention) where nearly 70% of the patches (N = 535) are owned by private landowners who manage them to harvest pine nuts, cork, and Wrewood, for coal making, cattle raising, and to a lesser extent, beekeeping and agriculture. The publicly owned patches are intensively used for recreation. As a consequence, the vegetation physiognomy and conservation status in most forest stands is impoverished, with low shrub diversity and coverage and none or very low natural tree regeneration. Furthermore, patch size, connectedness and patch fractal dimension (i.e. microhabitat diversity) are all very low. However, the botanic richness is worth mentioning: 1,032 plant taxa have been identiWed, of which 70 are catalogued in an oYcial red list, 39 are relevant chorological novelties, and one was newly described for science. Therefore, and interestingly, the remnant forest patches in the studied area can be regarded as relevant biodiversity reservoirs. The project reported here constitutes an important baseline for developing true conservation action plans and provides an opportunity to address the potential ecological and biological eVects of fragmentation to plant genes, species, populations and communities, at the regional scale of the study, which are enhanced by the emergent landscape genetics and landscape ecology analytical tools.
Keywords: Biodiversity; Connectivity; fragstats; Habitat fragmentation; habitat loss; isolation; Mediterranean vegetation

Descriptive analysis of the ‘relictual’ Mediterranean landscape in the Guadalquivir River valley (southern Spain): a baseline for scientific research and the development of conservation action plans - Aparicio, Abelardo (Biodiversity and Conservation, 2007)
Landscape fragmentation is ancient and severe in the countryside of the Guadalquivir river valley (Western Andalusia, Southern Spain). BIANDOCC is a project that aims to inventory all the forest patches embedded in this anthropogenic area to record quantitative, qualitative, and descriptive information about management, conservation status, vegetation physiognomy and Xoristic richness. We have characterized a ‘relictual’ landscape (t1% of habitat retention) where nearly 70% of the patches (N = 535) are owned by private landowners who manage them to harvest pine nuts, cork, and Wrewood, for coal making, cattle raising, and to a lesser extent, beekeeping and agriculture. The publicly owned patches are intensively used for recreation. As a consequence, the vegetation physiognomy and conservation status in most forest stands is impoverished, with low shrub diversity and coverage and none or very low natural tree regeneration. Furthermore, patch size, connectedness and patch fractal dimension (i.e. microhabitat diversity) are all very low. However, the botanic richness is worth mentioning: 1,032 plant taxa have been identiWed, of which 70 are catalogued in an oYcial red list, 39 are relevant chorological novelties, and one was newly described for science. Therefore, and interestingly, the remnant forest patches in the studied area can be regarded as relevant biodiversity reservoirs. The project reported here constitutes an important baseline for developing true conservation action plans and provides an opportunity to address the potential ecological and biological eVects of fragmentation to plant genes, species, populations and communities, at the regional scale of the study, which are enhanced by the emergent landscape genetics and landscape ecology analytical tools.
Keywords: Biodiversity; Connectivity; fragstats; Habitat fragmentation; habitat loss; isolation; Mediterranean vegetation